2022
DOI: 10.1021/acsomega.2c03071
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Simulations of Thermomechanical Properties of Epoxy-Amine Resins

Abstract: All-atom molecular dynamics (MD) simulations were performed with the CHARMM force field to characterize various epoxy resins, such as aliphatic and bisphenol-based resins. A multistep cross-linking algorithm was established, and key properties such as density, glass temperature, and elastic modulus were calculated. A quantitative comparison was made and was proven to be in good agreement with experimental data, with average absolute deviations between experiments and molecular simulation comprised between 2% a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 57 publications
(98 reference statements)
1
11
0
Order By: Relevance
“…This investigation of the impact of degree of cross-linking is possible by molecular simulation but is not experimentally controlled. The methodology used for building a three-dimensional cross-linked polymer network has been published in ref . Figure a shows the density of the cured DGEBA+IPDA epoxy resin as a function of the conversion rate at 300 and 400 K. For both temperatures, molecular simulations reproduce the increase of density with increasing degree of cross-linking as expected from the volume shrinkage due the increasing formation of covalent bonds.…”
Section: Resultsmentioning
confidence: 97%
“…This investigation of the impact of degree of cross-linking is possible by molecular simulation but is not experimentally controlled. The methodology used for building a three-dimensional cross-linked polymer network has been published in ref . Figure a shows the density of the cured DGEBA+IPDA epoxy resin as a function of the conversion rate at 300 and 400 K. For both temperatures, molecular simulations reproduce the increase of density with increasing degree of cross-linking as expected from the volume shrinkage due the increasing formation of covalent bonds.…”
Section: Resultsmentioning
confidence: 97%
“…These epoxy polymers, belonging to a class of thermoset polymers, are used ubiquitously as matrix materials for their high thermostability, strong adhesion to glass/carbon fibers, and high mechanical strength. Even though numerous research studies have been conducted on these materials, , a detailed understanding of linking molecular bond level dynamics with global continuum-level response needs to be obtained, which is being addressed in this work. In this regard, it should be noted that even though there exist numerous literature studies linking bond level information with global response for thermoplastic polymers, , there appears to be almost no such literature study for thermoset polymeric systems exhibiting a complex network structure.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies on epoxy resins have correlated the effect of the cross-link density on the thermal and mechanical properties using both experimental and molecular dynamic (MD) simulations, , ,, in which it has been observed that increasing the percentage of cross-linking results in an increase in the elastic stiffness along with that in glass transition temperature ( T g ). It has also been demonstrated that the resin monomer functionality, cross-linker length, , and type of hardeners used for cross-linking , all influence the mechanical performance of the resin system. Typically, it is believed that with an increase in cross-linking, there is the formation of covalent bonds within the system (as a result of the formation of a molecular network architecture), thereby suggesting that an increase in the network among moieties in the cross-linked molecular structure improves the mechanical response of the epoxy resin system.…”
Section: Introductionmentioning
confidence: 99%
“…Epoxy resin, an important component of FRP, has been a common target for MD simulations. Numerous studies have been conducted to explore the cross‐linking reactions, mechanical behavior, and thermodynamic properties of epoxy resins with the aid of MD simulations for the past decade with various forcefields including DREIDING, AMBER, CHARMM, CVFF, and PCFF 23–28 . The focus has recently been switched from epoxy resin to the epoxy interface.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have been conducted to explore the cross-linking reactions, mechanical behavior, and thermodynamic properties of epoxy resins with the aid of MD simulations for the past decade with various forcefields including DREIDING, AMBER, CHARMM, CVFF, and PCFF. [23][24][25][26][27][28] The focus has recently been switched from epoxy resin to the epoxy interface. Yu et al 29 investigated the degradation mechanism of the epoxy-cement interface with the CVFF and CSH-FF forcefield and found that water molecules degraded the interface and changed the failure mode to interfacial debonding.…”
Section: Introductionmentioning
confidence: 99%